Optical solitons and other solutions to the conformable space-time fractional complex Ginzburg-Landau equation under Kerr law nonlinearity - Sulaiman, Tukur Abdulkadir; Baskonus, Haci Mehmet; Bulut, Hasan (Indian Acad Sciences, 2018)
This study reveals the dark, bright, combined dark-bright, singular, combined singular optical solitons and singular periodic solutions to the conformable space-time fractional complex Ginzburg-Landau equation. We reach such solutions via the powerful extended sinh-Gordon equation expansion method (ShGEEM). Constraint conditions that guarantee the existence of valid solitary wave solutions are given. Under suitable choice of the parameter values, interesting three-dimensional graphs of some of the obtained solutions are plotted.
Keywords: Sinh-Gordon equation; Ginzburg-Landau equation; optical soliton; periodic wave